PENINGKATAN KETERAMPILAN MENULIS KARANGAN NARASI PADA PEMBELAJARAN TEMATIK TERPADU MENGGUNAKAN MODEL PBL DI KELAS IV SDN 47 KOTO LAMO KABUPATEN PESISIR SELATAN - Nurmeliza , Jadtri; Rossa, Rona (LP2M Universitas Adzkia, 2024)
Students’ narrative essay writing skills are still low, the reason to write is not optimal in gulding students whwn learning to write narrative essay. Writing narrative essay’s using teh problem based learning (PBL) model for fourth grade students of SD 47 Koto Lamo, Pesisir Selatan Regency. The purpose of this study is to describe the improvement of narrative essay writing skills integrated thematic learning using teh Problem Based Learning (PBL) model at the pre-writing, writing and post-writing stages in fourth grade elementary school studens. This rsearch uses classroom action research with qualitative and quantitative approaches planning in the arrangement includess 1) research, 2) research subject, 3) time, 4) reserch flaw, 5) planning, 6) implementation, 7) observastion, 8) reflection. The research subject were fourth grade students of studens SDN 47 Koto Lamo, Pesisir Selatan Regency, totalling 16 people, 7 boys adan 9 girls, the learning process wass carried out by researchers, class teachers, and colleaguses as observers. The data were collected using the observation technique of students learning reseach results. The results of the research from it 16 studebts in the first cycle of pre writing stages obtained a techinique of 58,6% with poor criteria (K) and the post writing stage they obtained apersentage of 58,91% with poor criteria (K), while in cycle 2 in the pre writing and writing stages get a persentage of 92,5% with very good criteria (A) and at the post writing stage it gets a persentage of 73,82% (B) this means that the implemenation of integrated thematic laeraning using the problem based learning (PBL) model can inprove narrative essay writing skills students. From the results obtained, it can be conciuded that integrated thematic learning using the problem based learning (PBL) model can improve students narritive writing skills in grade IV SDN 47 Koto Lamo, Pesisir Selatan Regency for this reason, the skills of writing narrative essay in tegreted thematic learning can use theproblem based leraning (PBL) model.